Analysis of contested narratives in Cui Yingjie case - Luping Zhang (Wolters Kluwer Medknow Publications, 2017)
This paper endeavors to explore how to analyze the lateral difference between factual narrative texts to the same case, as well as the narrative mechanism that caused such lateral difference. It applies its four perspectives of the story model, namely, (1) coverage, (2) coherence, (3) uniqueness, and (4) goodness of fit to the study of evidence in Cui Yingjie case. The author explores why different interpretations the prosecution and defense adopted in the trial of the case could not provide a reliable logic to illustrate the necessity of their statements. In light of the story model, this paper explains the mechanism behind the techniques of evidence presentation both prosecution and defense adopted in the trial of Cui Yingjie case.